Analisis Kepatuhan Penggunaan Obat Antihipertensi Pasien Hipertensi Rawat Jalan Usia Geriatri Terhadap Tekanan Darah - Novi Tartila Akri; Nurmainah Nurmainah; Mohammad Andrie (Journal Syifa Sciences and Clinical Research, 2022)
Medication adherence is an important factor in controlling blood pressure in hypertensive patients. The purpose of this study was to analyze the correlation between therapy adherence and control of blood pressure factors, as well as to analyze the correlation between gender and gender on the adherence of geriatric patients in undergoing antihypertensive treatment. The method used is analytical observational method by designing a cohort study research. Data was collected retrospectively, manual and electronic data collection (medical records). Measurement of compliance using the Medication Possession Ratio (MPR) method. Data analysis used Chi-Square test with SPSS. The results showed that patients who visited the Outpatient Installation of RSUD dr.Rubini tended to be female (60.6%), patients with monotherapy regimen (50.7%), frequency of drug administration 1x1 a day (90.1%), and patients with uncontrolled blood pressure (73.2%). As many as 18.3% of patients adhered to antihypertensive treatment. Chi-square analysis showed that there was a significant relationship between gender (p=0.05) and blood pressure control (p=0.032), while the results of therapy analysis were not statistically significant with p-values of 0.387 and 1,000 ( 0, 05). It was concluded that there was a correlation between gender and blood pressure control on patient compliance in undergoing treatment.